In Situ Measurement of Temperature Distributions in a Li-ion Cell during Internal Short Circuit and Thermal Runaway. Issue 9 (6th September 2021) - Huang, Shan; Du, Zhijia; Zhou, Qian; Snyder, Kent; Liu, Siyi; Zhang, Guangsheng
Abstract : Here we report in situ measurement of temperature distributions in a 2.5-Ah pouch format Li-ion cell during internal short circuit (ISC) and thermal runaway. The ISC and thermal runaway were triggered by nail penetration. The local temperatures were measured by embedded K type micro thermocouples in the middle layer of the experimental Li-ion cell. Highly non-uniform temperature distributions were observed during ISC and thermal runaway as compared with those during constant current discharging and external short circuit. The in situ measurement also captured details of how thermal runaway started from the ISC location and spread to the entire cell in a few seconds. Moreover, the comparison between ISC without thermal runaway and ISC with thermal runaway suggests that internal short circuit resistance plays a critical role in the risk of thermal runaway.